Transforming Emergency Education to Accredited School: A Case Study of SMAN 4 Takari - Ferry H. Umbu Tamu; Orip Atte (Wise Education, 2024)
The persistent issue of low education quality in Indonesia has long been a significant challenge. SMAN 4 Takari, originally a filial class of SMAN 2 Takari, officially became independent on July 5, 2021. The primary challenges include inadequate infrastructure and lack of accreditation, impacting the quality of education received by students. This community service activity aims to improve the quality of education at SMAN 4 Takari by enhancing infrastructure, preparing for accreditation, and increasing community and stakeholder involvement. The project employs a descriptive qualitative approach using data collection techniques such as observation, interviews, surveys, and documentation. The process includes initial preparation through the formation of an accreditation committee, task allocation, document collection, infrastructure development, and the accreditation process. The project led to significant improvements in the school's infrastructure, such as the construction of the student council room, health unit room, counseling room, and administrative office. All necessary documents for accreditation were prepared and uploaded to the DIA application in SisPenA. The school successfully obtained accreditation with a score of 79 and a